Relação entre comprimento craniocaudal e diãmetro da vesícula embrionária/fetal com idade de gestação por meio de avaliação ultra-sonográfica em ovino da raça Bergamácia - Chalhoub, M. [UNESP]; Prestes, Nereu Carlos [UNESP]; Lopes, Maria Denise [UNESP]; Ribeiro Filho, A. L.; Lopes, R. M. [UNESP]; Trinca, L. A. (FapUNIFESP (SciELO), 2001)
This study aimed to relate embryonic/fetal vesicle diameter (EVD) and crown-rump length (CRL) to gestational age in ewes from the 15 th to the 45 th day of pregnancy. Nineteen adult Bergamácia ewes with synchronized estrus were mated by the same male. Ultrasonographic evaluations were performed every 24 hours from the 15 th to the 30 th day after mating and every five days from the 30 th to the 45 th day using 5.0 and 7.5MHZ linear transducers. Average daily growth of EVD and CRL were 1.40mm and 1.33mm, respectively. The inverse calibration obtained for EVD was: Days = -11 + 50(0.1 + 0.04log EVD) 1/2 with R 2 = 0.85, and for CRL was: Days = 13.63 + 12.5(- 0.71 + 0.16CRL) 1/2 with R 2 = 0.93. Both EVD and CRL obtained by ultrasonography are useful measurements that allow the prediction of gestational age in Bergamácia ewes.
Relationship between crown-rump length and embryonic/fetal vesicle diameter with gestational age in ovine of Bergamácia breed by ultrasonography
Keywords: Crown-rump; Embryonic/fetal vesicle; Pregnancy; Sheep; Ultrasonography